"Crowding in" or "crowding out"? An examination of the impact of the welfare state on generalized social trust. (21st February 2013) - Brewer, Kathryne B; Oh, Hans; Sharma, Shilpi
Abstract : Generalized social trust is correlated with increased levels of civic engagement, lower crime rates, and greater economic growth. Many scholars believe that equality provides the conditions in which social trust can flourish. Thus, welfare programs might be one way to generate social trust. However, the relationship between social spending and trust is contested: Some argue it is negative, while others argue it is positive. This study examined the effects of total social welfare expenditures on social trust in 18 OECD countries, holding constant individual characteristics, country characteristics, and country and year effects. Fixed effects analyses indicate that every additional percent of gross domestic product spent on social expenditures 5 years prior is associated with a 4.7 percent increased likelihood that respondents of that country will endorse trusting other people. Further testing for reverse causality found no significant association between trust and later social expenditures, supporting the claim that expenditures drive trust instead of the reverse.